Metal Contamination of Stream Waters under the Impact of Tanneries - RODRIGUES, MARIA LUCIA KOLOWSKI; FORMOSO, MILTON LUIZ LAQUINTINIE (Pesquisas em Geociências, 2006)
<!– .p text-align: justify; –> This study evaluated the contamination of water samples from Cadeia and Feitoria rivers (Rio Grande do Sul State, Brazil), affected by tannery activities. From July 1999 to April 2000, four sampling campaigns were performed at ten sites in order to evaluate selected metals and ancillary physicochemical variables. Sample preservation and analyses followed recommendations of the Standard Methods. Factor analysis was used to obtain statistical indexes representing the contamination degree of waters evaluated. The information was summarized in two principal components. The first, which accounted for 50% of the total variance, was associated to a tannery contribution and generated a contamination index. Total, Suspended and Dissolved Solids, Dissolved Oxygen, Conductivity, Chromium, Manganese, Copper, Nickel, Sodium, Calcium, Potassium, and Magnesium were the well-correlated variables with this first component. The water quality decreased from headwaters up to mouth along both streams, but the most contaminated sites were located at the lower reach of Feitoria river (Ivoti and Lindolfo Collor cities), where tanneries are concentrated. After the entrainment of Feitoria waters (São Sebastião do Caí municipality), Cadeia river also presented an increased contamination degree. The application of statistical randomization tests highlighted these same sites as significantly distinct from the others. Water contamination also showed association to flow variations, and a poorer water quality was observed during the dry period (January). The second component, in which Iron, Aluminum, and Suspended Solids were the relevant variables, was loaded with 15% of the total variance. It was linked to natural events, since higher factor scores in this component were obtained during a period of increased water discharge (October), which caused resuspension and entrainment of solid material to the rivers bed. As a final result of the study, sampling stations were classified according to the contamination degree, and graphically represented on a basin map, which synthesized the environmental diagnosis.